2020
DOI: 10.12659/msm.925579
|View full text |Cite
|
Sign up to set email alerts
|

Biological Network Model of Effect of Chronic Intermittent Hypoxia on Spermatogenesis in Rats

Abstract: Background The aim of this study was to explore the effect of obstructive sleep apnea hypopnea syndrome (OSAHS) on spermatogenesis and the effects of the expression of related proteins. Material/Methods Rats in Group A were normoxic (exposed to a normal level of oxygen). Rats in Group B were exposed to intermittent hypoxia. After 6 weeks, the rats were killed and their epididymides were removed. The epididymis of one testis was used to test indices of semen quality. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…To improve the reliability of the data obtained, each PPI was filtered further, with a minimum interaction score of 0.40. The filtered PPI was used for network construction and analyses (Wang, Gong, Deng, et al., 2020; Wang, Gong, Meng, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the reliability of the data obtained, each PPI was filtered further, with a minimum interaction score of 0.40. The filtered PPI was used for network construction and analyses (Wang, Gong, Deng, et al., 2020; Wang, Gong, Meng, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The concept of network pharmacology is derived from the introduction of systems biology and the application of bioinformatics, as well as from the ‘omics’ theories related to the development of modern genomics, proteomics, and metabolomics. Based on the ‘disease‐gene‐target‐drug’ interaction network, a network analysis method was used to observe the intervention and influence of drugs on the disease network, and to determine the synergistic effect of multiple drugs (Wang, Gong, Deng, et al., 2020; Wang, Gong, Meng, et al, 2020). First, network pharmacology was used to predict key active ingredients and targets.…”
Section: Introductionmentioning
confidence: 99%
“…The sperm quality outcome measures are the sperm concentration, motility, morphology, semen volume, viability and DNA fragmentation, which are the parameters most frequently used in clinical settings ( Schisterman et al, 2020 ). Growing evidence has shown that hypoxia has adverse effects on sperm quality in several species, including rodents, livestock, Drosophila, fish, and humans ( Wang et al, 2016 ; Cofre et al, 2018 ; Wang J. et al, 2020 ). In rats and mice, acute, intermittent and chronic hypoxia reduced the total sperm concentration and sperm motility while increasing the rates of sperm DNA fragmentation and abnormal sperm morphology ( Vargas et al, 2011 ; Torres et al, 2014 ; Bai et al, 2018 ; Wang J. et al, 2020 ; Ma et al, 2021 ).…”
Section: Reproductive Consequences Of Hypoxiamentioning
confidence: 99%
“…Growing evidence has shown that hypoxia has adverse effects on sperm quality in several species, including rodents, livestock, Drosophila, fish, and humans ( Wang et al, 2016 ; Cofre et al, 2018 ; Wang J. et al, 2020 ). In rats and mice, acute, intermittent and chronic hypoxia reduced the total sperm concentration and sperm motility while increasing the rates of sperm DNA fragmentation and abnormal sperm morphology ( Vargas et al, 2011 ; Torres et al, 2014 ; Bai et al, 2018 ; Wang J. et al, 2020 ; Ma et al, 2021 ). Hypoxia in rams led to a lower sperm count, sperm progressive motility and viability than in normoxic rams ( Cofre et al, 2018 ).…”
Section: Reproductive Consequences Of Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation